'Who wants to know?': a field experiment to assess discrimination in freedom of information regimes - Velasco, Rafael Antonio Braem (2016)
Scholars and practitioners contend that the process of obtaining public information from governmental agencies should be applicant blind and non-discriminatory. According to this contention, Brazil’s FOI Law renders discrimination more likely because requesters are forced to provide mandatory identity requirements. This study puts claims about identity blindness to the test. It presents two field experiments conducted in Brazil, one at the municipal level and the other at the federal level. A total of 548 requests were sent to 361 City Halls and 94 federal agencies. Results show that at the Municipal level discrimination is statistically significant, as levels of responses for requests sent by individuals affiliated with a prominent Brazilian research institution are higher than those sent by ‘ordinary’ citizens. These findings suggest that public administrators are ‘Googling’ requesters and discrimination on the basis of identity. In effect, identity requirements may inhibit a broader and more efficacious use of FOI regimes in countries and jurisdictions where identities are disclosed to authorities.